Обряд обдаровування, або Огляд пісень сліпців-жебраків - Клеут, М. (Народна творчість та етнологія, 2012)
The article makes a special effort to define mendicant songs as a special genre of folk lyric poetry on Марiiа Kleut the basis of three criteria: (1) as a verbal (and musical) part of mendicant customs, which have certain characteristics of ritual (a specific place where alms are sought, a specific time when this is done, a certain form of behavior; (2) from the standpoint of their functionality and (3) in view of their immanent poetic features.